Neurological consultations and diagnoses in a large, dedicated COVID-19 university hospital - STUDART-NETO, Adalberto; GUEDES, Bruno Fukelmann; TUMA, Raphael de Luca e; CAMELO, Antonio Edvan, FILHO; KUBOTA, Gabriel Taricani; IEPSEN, Bruno Diógenes; MOREIRA, Gabriela Pantaleão; RODRIGUES, Júlia Chartouni; FERRARI, Maíra Medeiros Honorato; CARRA, Rafael Bernhart; SPERA, Raphael Ribeiro; OKU, Mariana Hiromi Manoel; TERRIM, Sara; LOPES, Cesar Castello Branco; PASSOS, Carlos Eduardo Borges, NETO; FIORENTINO, Matheus Dalben; DE SOUZA, Julia Carvalhinho Carlos; BAIMA, José Pedro Soares; DA SILVA, Tomás Fraga Ferreira; MORENO, Cristiane Araujo Martins; SILVA, Andre Macedo Serafim; HEISE, Carlos Otto; MENDONÇA, Rodrigo Holanda; FORTINI, Ida; SMID, Jerusa; ADONI, Tarso; GONÇALVES, Marcia Rubia Rodrigues; PEREIRA, Samira Luisa Apóstolos; PINTO, Lecio Figueira; GOMES, Helio Rodrigues; ZANOTELI, Edmar; BRUCKI, Sonia Maria Dozzi; CONFORTO, Adriana Bastos; CASTRO, Luiz Henrique Martins; NITRINI, Ricardo (Arquivos de Neuro-Psiquiatria, 2020)
Background: More than one-third of COVID-19 patients present neurological symptoms ranging from anosmia to stroke and encephalopathy. Furthermore, pre-existing neurological conditions may require special treatment and may be associated with worse outcomes. Notwithstanding, the role of neurologists in COVID-19 is probably underrecognized. Objective: The aim of this study was to report the reasons for requesting neurological consultations by internists and intensivists in a COVID-19-dedicated hospital. Methods: This retrospective study was carried out at Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, Brazil, a 900-bed COVID-19 dedicated center (including 300 intensive care unit beds). COVID-19 diagnosis was confirmed by SARS-CoV-2-RT-PCR in nasal swabs. All inpatient neurology consultations between March 23rd and May 23rd, 2020 were analyzed. Neurologists performed the neurological exam, assessed all available data to diagnose the neurological condition, and requested additional tests deemed necessary. Difficult diagnoses were established in consensus meetings. After diagnosis, neurologists were involved in the treatment. Results: Neurological consultations were requested for 89 out of 1,208 (7.4%) inpatient COVID admissions during that period. Main neurological diagnoses included: encephalopathy (44.4%), stroke (16.7%), previous neurological diseases (9.0%), seizures (9.0%), neuromuscular disorders (5.6%), other acute brain lesions (3.4%), and other mild nonspecific symptoms (11.2%). Conclusions: Most neurological consultations in a COVID-19-dedicated hospital were requested for severe conditions that could have an impact on the outcome. First-line doctors should be able to recognize neurological symptoms; neurologists are important members of the medical team in COVID-19 hospital care.
Keywords: Coronavirus Infections; COVID-19; Neurology; Seizures; Stroke; Metabolic Encephalopathy; Neuromuscular Diseases